2002
DOI: 10.1021/jf025645s
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Anthocyanins from Pulp Wash of Pigmented Oranges by Concentration on Resins

Abstract: A pulp wash (PW) coming from a plant for citrus processing of pigmented oranges was utilized as a starting material to recover anthocyanins, using the procedure of concentration on resin. Six commercial food-grade resins were tested to find the more suitable ones for adsorbing anthocyanins, and 96% ethanol was used as eluent for desorbing them. An automated experimental apparatus was developed to perform the adsorption-desorption procedure on column. The kinetics results in a batch system and experiments on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 18 publications
6
49
0
Order By: Relevance
“…2. Significant positive correlation between dosing of potato peel extract and SOD levels in rats treated with CCl 4 3. histopathological studies showed that CCl 4 induced a remarkable degeneration in hepatocytes and focal necrosis. However, in general, lesions were markedly diminished in rats that were pre-administered with potato peel extract prior CCl 4 administration.…”
Section: {Arora 1994 #86730}mentioning
confidence: 93%
See 2 more Smart Citations
“…2. Significant positive correlation between dosing of potato peel extract and SOD levels in rats treated with CCl 4 3. histopathological studies showed that CCl 4 induced a remarkable degeneration in hepatocytes and focal necrosis. However, in general, lesions were markedly diminished in rats that were pre-administered with potato peel extract prior CCl 4 administration.…”
Section: {Arora 1994 #86730}mentioning
confidence: 93%
“…Lignin content was found to decrease but total dietary fiber content was unaffected in extruded abrasion peels. 4 Protective role of the potato peel extract against induced liver injury using CCL 4 in rats.…”
Section: {Arora 1994 #86730}mentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, the pigments may be purified and concentrated by sorptive binding onto a resin surface and subsequent desorption with ethanol. The eluates recovered under such conditions further contain hesperidin and hydroxycinnamic acids, which may act as co-pigments and stabilize anthocyanins (Di Mauro et al, 2002). The same group further studied the potential of liquid residues, i.e., wastewater originating from citrus processing, for the recovery of valuable phenolic compounds.…”
Section: Application Of Adsorbent Resins and Ion Exchangers For The Rmentioning
confidence: 99%
“…Experimental equilibrium data were fitted to the Langmuir and Freundlich isotherm models to compare adsorption of resins (Mauro et al, 2002). These isotherms are represented mathematically as:…”
Section: Static Adsorption Isotherms Considering the High Volatilitymentioning
confidence: 99%